Dictators and democrats masses, elites, and regime change - Haggard, Stephan; Kaufman, Robert R. (Princeton University Press, 2016)
From the 1980s through the first decade of the twenty-first century, the spread of democracy across the developing and post-Communist worlds transformed the global political landscape. What drove these changes and what determined whether the emerging democracies would stabilize or revert to authoritarian rule? Dictators and Democrats takes a comprehensive look at the transitions to and from democracy in recent decades. Deploying both statistical and qualitative analysis, Stephen Haggard and Robert Kaufman engage with theories of democratic change and advocate approaches that emphasize political and institutional factors. While inequality has been a prominent explanation for democratic transitions, the authors argue that its role has been limited, and elites as well as masses can drive regime change. Examining seventy-eight cases of democratic transition and twenty-five reversions since 1980, Haggard and Kaufman show how differences in authoritarian regimes and organizational capabilities shape popular protest and elite initiatives in transitions to democracy, and how institutional weaknesses cause some democracies to fail.